2017
DOI: 10.1107/s2053229617001486
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular hydrogen-bonding patterns in 1:1 cocrystals of 5-fluorouracil with 4-methylbenzoic acid and 3-nitrobenzoic acid

Abstract: The design of a pharmaceutical cocrystal is based on the identification of specific hydrogen-bond donor and acceptor groups in active pharmaceutical ingredients (APIs) in order to choose a `complementary interacting' molecule that can act as an efficient coformer. 5-Fluorouracil (5FU) is a pyrimidine derivative with two N-H donors and C=O acceptors and shows a diversity of hydrogen-bonding motifs. Two 1:1 cocrystals of 5-fluorouracil (5FU), namely 5-fluorouracil-4-methylbenzoic acid (5FU-MBA), CHFNO·CHO, (I), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…This leads to the formation of a supramolecular ribbon of 5FU molecules parallel to the (013) plane. Similar types of R 2 2 (8) homosynthons (N-HÁ Á ÁO) and ribbons are observed in 5-fluorouracil-3-hydroxybenzoic acid, 5-fluorouracil-4-aminobenzoic acid and 5-fluorouracil-cinnamic acid (Dai et al, 2016), and 5-fluorouracil-4-methyl-benzoic acid (Mohana et al, 2017). In cocrystal (I), the supramolecular ribbon also contains an R 2 3 (9) motif involving N-HÁ Á ÁO and C-HÁ Á ÁO hydrogen bonds, generating a quadruple DADA (D is a donor and A is an acceptor) array of hydrogen bonds.…”
Section: Resultsmentioning
confidence: 64%
See 2 more Smart Citations
“…This leads to the formation of a supramolecular ribbon of 5FU molecules parallel to the (013) plane. Similar types of R 2 2 (8) homosynthons (N-HÁ Á ÁO) and ribbons are observed in 5-fluorouracil-3-hydroxybenzoic acid, 5-fluorouracil-4-aminobenzoic acid and 5-fluorouracil-cinnamic acid (Dai et al, 2016), and 5-fluorouracil-4-methyl-benzoic acid (Mohana et al, 2017). In cocrystal (I), the supramolecular ribbon also contains an R 2 3 (9) motif involving N-HÁ Á ÁO and C-HÁ Á ÁO hydrogen bonds, generating a quadruple DADA (D is a donor and A is an acceptor) array of hydrogen bonds.…”
Section: Resultsmentioning
confidence: 64%
“…The 5FU molecules are connected through a pair of N1-H1Á Á ÁO1 i and N3-H3Á Á ÁO1 ii hydrogen bonds to form an R 2 2 (8) dimeric homosynthon (see Table 3 for details and symmetry codes). Similar types of R 2 2 (8) homosynthons (N-HÁ Á ÁO) and ribbons are observed in 5-fluorouracil-3-hydroxybenzoic acid, 5-fluorouracil-4-aminobenzoic acid and 5-fluorouracil-cinnamic acid (Dai et al, 2016), and 5-fluorouracil-4-methylbenzoic acid (Mohana et al, 2017). This leads to the formation of a supramolecular ribbon of 5FU molecules parallel to the (021) plane.…”
Section: Tablementioning
confidence: 63%
See 1 more Smart Citation
“…The release of 5FU from the hydrogels was dependent on the crosslinking density and pH of the release media. The FTIR result for the 5FU-loaded hydrogels show that the 5FU amine group and inulin polymer hydroxyl may have formed a hydrogen bond interaction [71,83,84]. This polymer–drug interaction may have resulted in slow drug release from the hydrogel due to entrapment of the remaining drug in the gel network (Figure 2C,D).…”
Section: Resultsmentioning
confidence: 99%
“…Newman [ 133 ] has summarized various methods reported in the literature to obtain various solid forms such as polymorphs, salts, cocrystals and amorphous solid dispersions [ 133 ]. Though hydrogen-bonding motif structures play a significant role in stabilizing the crystal structures of cocrystals [ 134 , 135 , 136 , 137 , 138 , 139 ], in some cases, evaluation of crystal structures of some cocrystals synthesized using techniques such as Solution crystallization, mechanocrystallization and hot-stage microscopy showed that these cocrystals do not possess hydrogen-bonding motifs as given by Crystal Engineering principles [ 124 ]. Therefore, a suitable coformer screening technique is highly essential for a cocrystallization process.…”
Section: Screening Methods For Cocrystalsmentioning
confidence: 99%